ECOLOGICAL SELF-SUFFICIENCY OF THE INSTITUTION OF HIGHER EDUCATIONAS AN ECOLOGICAL AND ECONOMIC BASIS OF ITS DEVELOPMENT - VOVK, OLENA; SYMAK, ANASTASIYA; PASHKEVYCH, VOLODYMYR; SYMAK, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2022)
From the standpoint of environmental theory, the concept of environmental self-sufficiency of higher education institution (HEI) can be interpreted as an essential attribute of any civilized scientific (educational, social, etc.) community, which is a form of management of internal and (or) external natural and material resources with maximum environmental and economic benefits for ourselves. In the scientific literature there is a classification of well-known in world practice models of organization of such economic activities, which is based on relations between all stakeholders in this process, which includes central government and local government: for HEI, in general, and "Lviv Polytechnic", in particular, the support is on the state level and the Ministry of Education and Science of Ukraine and the city administration. The article considers the most common world practices and approaches in the organization of environmental self-sufficiency of organizations, in particular, higher education institutions, notes their characteristics, as well as strengths and weaknesses. Statistical data are presented and the sources of ecological self-sufficiency of HEI in Ukraine and abroad are compared, and the peculiarities of the current models of ecological self-sufficiency of the HEI economic zone of Lviv are compared and analysed. In addition, the article presents an analysis of current innovations in the context of the effectiveness of the resource approach to the system of environmental self-sufficiency of the HEI economic zone. Also the main obstacles to the implementation of the principle of environmental self-sufficiency of the HEI economic zone and difficulties in the formation of internal budgets are outlined of it. The issues of planning, implementation, control, optimization and improvement of environmental self-sufficiency of organizations in general, and HEI economic zones in particular, through self-financing as the basis of self-government in terms of environmental self-sufficiency are also considered. The variant of constant sources of realization of basic and (or) primary level of ecological self-sufficiency of the budget of ZVO is offered, the description of advantages and lacks of the presented variant of HEI ecological self-sufficiency is given, and also requirements for maintenance of functioning of such mechanism on the example of "Lviv Polytechnic" and formulated relevant conclusions from this study.